Splay-foot in cattle - Schalles, R.R.; Markham, R.W.; Leipold, H.W.; Spire, M.F. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Angular limb deformity, observed in several breeds of cattle, results in a knock-kneed and splay-footed condition in the front legs. This study shows that angular limb deformity is a congenital structural defect, inherited as a simple, autosomal, recessive trait.
Keywords: Beef; Splay-foot; Angular limb deformity